2015
DOI: 10.1128/mbio.01866-15
|View full text |Cite
|
Sign up to set email alerts
|

IS 26 -Mediated Precise Excision of the IS 26 - aphA1a Translocatable Unit

Abstract: We recently showed that, in the absence of RecA-dependent homologous recombination, the Tnp26 transposase catalyzes cointegrate formation via a conservative reaction between two preexisting IS26, and this is strongly preferred over replicative transposition to a new site. Here, the reverse reaction was investigated by assaying for precise excision of the central region together with a single IS26 from a compound transposon bounded by IS26. In a recA mutant strain, Tn4352, a kanamycin resistance transposon carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 23 publications
6
71
0
Order By: Relevance
“…Theoretically, TU excision would require strand exchange between one inner and one outer IS end of the transposon, that is, between two left or two right IS termini, but only the left IS 26 (as shown in Table ) was required to produce active Tnp26 for excision to occur. This is consistent with cis action of Tnp26, and it was predicted that the left ends of the two IS 26 in Tn 4352 B were involved in the reaction (Harmer and Hall, ). To examine this prediction, mutations were introduced at either the left, right or both outer ends of Tn 4352 B as shown in Table .…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Theoretically, TU excision would require strand exchange between one inner and one outer IS end of the transposon, that is, between two left or two right IS termini, but only the left IS 26 (as shown in Table ) was required to produce active Tnp26 for excision to occur. This is consistent with cis action of Tnp26, and it was predicted that the left ends of the two IS 26 in Tn 4352 B were involved in the reaction (Harmer and Hall, ). To examine this prediction, mutations were introduced at either the left, right or both outer ends of Tn 4352 B as shown in Table .…”
Section: Resultssupporting
confidence: 84%
“…In all cases, the two substituted right terminal bases were present. Hence, the TU had been formed from the wild‐type left‐hand IS 26 and the aphA1a ‐containing central fragment, and the sequence of the amplicon derived from the excised TU using primers aphA1‐A and aphA1‐B as described previously (Harmer and Hall, ) confirmed this. Hence, the outer right end is not required for the IS 26 ‐mediated excision of a TU from Tn 4352 B.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The frequency of pS28‐3 (which only confers resistance to florfenicol) declined in 2015, while plasmid pS121‐1b, a pS121‐1a variant devoid of the floR‐ containing region, was first detected the same year. The deletion of genomic regions flanked by IS26 elements has been regularly reported (Harmer et al ., ; He et al ., ) and support the hypothesis that pS121‐1b emerged directly from pS121‐1a through the excision of the floR ‐containing region. Our observation thus demonstrated that the exposure to antibiotic treatment has a direct, within‐year effect on the MGE prevalence in the pathogen's population, and that this prevalence is presumably connected to independent MGE acquisition patterns for different subclonal groups of the original sensitive clone.…”
Section: Discussionsupporting
confidence: 80%